MOLECULAR MARKERS IN GENETIC STUDIES AND BREEDING - E. K. Khlestkina (Вавиловский журнал генетики и селекции)
Back in the early decades in Genetics, it became clear that genetic markers may be useful in the analysis of complex traits. However, the low occurrence and a number of other shortcomings hampered wide application of classical genetic markers, and later then protein markers in the breeding. The latest generation of genetic markers (molecular or DNA markers) are characterized by frequent occurrence in the genome, and are based on universal (and hence highly demanded and constantly developing) methods of analysis. This became the key to the rapid development of genetics and breeding areas related to the use of DNA markers. This article provides a brief overview of the main types of molecular markers and the fields of their application.